View of the Metropolitan Church of St. Stephan in Vienna, from the high altar to the giant gate - Wilder, George Christian, 1797-1855 (artist):::Creator:::::::::::: (Ferd. Bauer; Vienna; Austria)
View of the interior of St. Stephanskirche in Vienna